2014
DOI: 10.1136/bcr-2013-203202
|View full text |Cite
|
Sign up to set email alerts
|

Severe systemic candidiasis following immunomodulation therapy in in vitro fertilisation-embryo transfer (IVF-ET)

Abstract: A 41-year-old nulliparous woman, with a medical history of unexplained infertility and multiple in vitro fertilisation (IVF) cycles with immunosuppressive therapy, was admitted to our tertiary obstetrics unit with sepsis at 18 weeks of pregnancy with dichorionic diamniotic twins.Candida glabratawas grown from her blood cultures, then subsequently from the liquor and placentae. She was treated with intravenous ambisome (amphotericin), but unfortunately, the infection resulted in the rupture of her membranes, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…of Health) can blockade Fc receptors on other immune cells, alter cytokine production and neutralize complement components, thereby possibly interfering with maternal immune defence mechanisms to pathogens. A salutary report describes a case of systemic candidiasis presenting at 18 weeks gestation resulting in fetal loss following administration of TNFα inhibitor, prednisolone and Intralipid during assisted reproduction ( Akhanoba, 2014 ). Around 40% of IVIg users will experience mild adverse events, and in serious cases can suffer from anaphylaxis ( Berger, 2013 ).…”
Section: Range Of ‘Immune’ Treatmentsmentioning
confidence: 99%
“…of Health) can blockade Fc receptors on other immune cells, alter cytokine production and neutralize complement components, thereby possibly interfering with maternal immune defence mechanisms to pathogens. A salutary report describes a case of systemic candidiasis presenting at 18 weeks gestation resulting in fetal loss following administration of TNFα inhibitor, prednisolone and Intralipid during assisted reproduction ( Akhanoba, 2014 ). Around 40% of IVIg users will experience mild adverse events, and in serious cases can suffer from anaphylaxis ( Berger, 2013 ).…”
Section: Range Of ‘Immune’ Treatmentsmentioning
confidence: 99%
“…The advantages of amphotericin B include that it crosses the placenta, has no reported adverse effects in humans [ 97 ], and is generally effective against C. glabrata . One case report showed that intravenous amphotericin B treatment resulted in pregnancy extension by 4 weeks and the delivery of live infants with no signs of inflammatory changes in the placenta or umbilical cord [ 89 ], although three other cases resulted in stillbirth [ 76 , 87 , 88 ]. Micafungin was used in one case, although its efficacy and safety in pregnant women are unclear, and whether it crosses the placenta remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries, well-known risk factors for sepsis are prolonged rupture of membranes, retained placenta or conception products, preterm labour, history of pelvic or other infection, interventions like cerclage or multiple vaginal examinations, diabetes, and anaemia (50,51). Maternal age over 35 years (52) and assisted reproductive techniques (53,54) can also increase risk of sepsis-related morbidity (17). Obesity, defined as a body mass index (BMI) > 30, is as well an established risk factor for surgical-site and nosocomial infections; it seems to negatively influence pregnancy-related outcome and to have substantial effects on immune surveillance (55,56).…”
Section: Risk Factors For Maternal Sepsismentioning
confidence: 99%